Analisis Pengaruh Faktor Kepariwisataan Terhadap Pendapatan Daerah di Provinsi Daerah Istimewa Yogyakarta Tahun 2010-2014 - Putra, Risky Didiet Mahendra, Dr. Didit Purnomo, MSi (2016)
This research aimed to analyze the effect of Numbers of Tourism,Numbers of tourism object, and the tourism supporting facilities, to regional income of Yogyakarta throughout the year 2010-2014. The analysis technique used in this study is a panel data regression. It used to determine the tourism factors that affect the Regional Income in special region of Yogyakarta along 2010-2014. Data panel is a combination of cross section that includes five region in Yogyakarta and time series during 5 years from 2010-2014. The results showed that the Common-Pooled Model (PLS) is a panel data regression model is most appropriate. Based on simultaneous test, Number of Tourism, Number of Tourism Object, and the tourism supporting facilities have an different impact on the regional income of Yogyakarta. Based on the effect validity test, Numbers of Tourism have significant positive effect on the Yogyakarta Regional Income, the Numbers of Tourism Object does not have a significant effect to the Yogyakarta Regional Income and Tourism Supporting Facilities has a significant negative effect on the regional income of Yogyakarta from 2010-2014. Keywords: Numbers of Tourism, Numbers of Tourism Object, Tourism Supporting Facilities, Regional Income